Quality and shelf life assessment of Pacific white shrimp (Litopenaeus vannamei) freshly harvested and stored on ice - Okpala, C.; Choo, W.; Dykes, Gary (2014)
Pacific white shrimps (Litopenaeus vannamei) are an important shrimp aquaculture species worldwide. To quantify the quality and shelf life of untreated shrimp is imperative prior to the application of preservative treatments. In this paper, the quality and shelf life of Pacific white shrimp freshly harvested from three different farms and stored on ice for up to 12 days was investigated. The titratable acidity (TA) of shrimp specimens exhibited significant decreases (P < 0.05) whereas the metric chroma (C), total colour difference (TCD), aerobic plate count (APC), trimethylamine (TMA-N) and total volatile basic – nitrogen (TVB-N), peroxide value (PV) and p-anisidine value (AnV) exhibited significant increases during iced storage (P < 0.05). The TMA-N and TVB-N were significantly correlated whereas temporal TMA-N/TVB-N ratio increased considerably (P < 0.05). While the PV and AnV significantly correlated (P < 0.05), the temporal PV/AnV ratio depicted how primary and secondary lipid oxidation of Pacific white shrimp could relate during iced storage of 12 days. The shelf life of ice stored Pacific white shrimps was determined to be 8 days. The information gained by this study could serve as baseline for preservative treatments applied to fresh shrimps.